2006
DOI: 10.1364/oe.14.010831
|View full text |Cite
|
Sign up to set email alerts
|

Feedback induced instabilities in a quantum dot semiconductor laser

Abstract: Abstract:We analyse the properties of GaAs based quantum dot semiconductor lasers emitting near 1310 nm. The line-width enhancement factor is shown to depend strongly on device temperature, ranging from 1.5 at 20 o C to 5 at 50 o C. With optical feedback from a distant reflector, devices remained stable at 20 o C but displayed a range of instabilities at 50 o C, including irregular power drop-outs and periodic pulsations, before entering a chaotic regime. Such dynamical features are unique to quantum dot laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…In the experiment, 6 the laser output was stable at low feedback strength. As the feedback level was increased, the laser displayed irregular sequences of dropouts at the delay frequency until it finally became a stable periodic oscillation.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…In the experiment, 6 the laser output was stable at low feedback strength. As the feedback level was increased, the laser displayed irregular sequences of dropouts at the delay frequency until it finally became a stable periodic oscillation.…”
mentioning
confidence: 82%
“…A strong optical feedback induces an instability range at high temperature. 6 These instabilities are very different from those commonly observed in quantum well lasers and cannot be explained in the frame of the conventional LK approach because experimental conditions include high pumping current, strong optical feedback, and a relatively long external cavity. The observations include periodic oscillations at the delay period, which evolve to chaos.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Carroll et al also reported a kind of stable dark pulse emission from a QD laser induced by the optical feedback from a distant reflector. 15 It was considered as a unique property of the QD semiconductor lasers. However, our experiment shows that with appropriate optical feedback, similar periodical dark pulses could also be obtained in a quantumwell semiconductor laser.…”
mentioning
confidence: 99%